2004
DOI: 10.1152/jn.01238.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of Whole Cell Patch and Sharp Electrodes by Simultaneous Recording From Single Spinal Neurons in Frog Tadpoles

Abstract: . A direct comparison of whole cell patch and sharp electrodes by simultaneous recording from single spinal neurons in frog tadpoles. J Neurophysiol 92: 380 -386, 2004; 10.1152/jn.01238.2003. High-impedance, sharp intracellular electrodes were compared with whole cell patch electrodes by recording from single spinal neurons in immobilized frog tadpoles. A range of neuron properties were examined using sharp or patch test electrodes while making simultaneous recordings with a second control patch electrode. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 20 publications
3
57
0
Order By: Relevance
“…This suggests that the relative conductance increase during network activity is determined by other factors than the cell size. In addition, the relation between the resting conductance and the conductance increase during network activity may be quenched by the artifactual shunt induced by the recording electrode, particularly in small cells (Li et al, 2004). We also found that the conductance increase for a given motoneuron was surprisingly similar during scratching and swimming.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This suggests that the relative conductance increase during network activity is determined by other factors than the cell size. In addition, the relation between the resting conductance and the conductance increase during network activity may be quenched by the artifactual shunt induced by the recording electrode, particularly in small cells (Li et al, 2004). We also found that the conductance increase for a given motoneuron was surprisingly similar during scratching and swimming.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast, insignificant or small changes in input conductance have been reported for motoneurons during locomotor activity (Shefchyk and Jordan, 1985;MacDonell et al, 2015). It has also been shown that conductance increases can be behavior-related (Perreault, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal parts of rostral myotomes were removed, and the roof of the nervous system was opened to the neurocoel to improve access. The methods for whole-cell patch using electrodes containing 0.1% neurobiotin (Vector Laboratories, Burlingame, CA) and Alexa Fluor-488 (Invitrogen, Eugene, OR), extracellular recording, and processing for neuronal anatomy have been described recently (Li et al, 2002(Li et al, , 2004b. Patch pipettes were filled with 0.1% neurobiotin and 0.1% Alexa Fluor 488 (Invitrogen) in intracellular solution (in mM: 100 K-gluconate, 2 MgCl 2 , 10 EGTA, 10 HEPES, 3 Na 2 ATP, 0.5 NaGTP adjusted to pH 7.3 with KOH) and had resistances of ϳ10 M⍀.…”
Section: Methodsmentioning
confidence: 99%
“…4(B) in Li et al (2004c). Typically, this burst follows a delay which is preceded by a single, initial spike (Fig.…”
Section: Delayed Bursting Neuronsmentioning
confidence: 96%
“…Nothing is known about the function of one class of possible neural canal receptor neuron (Dale et al, 1987). For the remaining neuron classes, using single-cell recordings (including a new wholecell patch recording method (Li et al, 2004c), in the spinal cord of immobilized tadpoles, we have defined the typespecific properties of individual neurons whose anatomical features were revealed by neurobiotin injection. These include: their passive and active responses to current injection, the transmitter pharmacology of synapses they make and receive (where some synaptic conductances have been studied in voltage-clamp recordings), and their activity during responses to sensory stimuli.…”
Section: Introductionmentioning
confidence: 99%